The first record of the rare Leucetta avocado sponge from Sangihe Islands, Indonesia - Rieuwpassa, Frets J.; Balansa, Walter (JASM, 2022)
Calcareous sponges represent the rarest class of marine sponges, constituting only 4% of the currently known sponge species globally. While abundant of demosponges have been reported from various locations in Indonesia, only 40 species of calcareous sponges have been identified in the country over the past 200 years. This suggests the rarity of these sponges and a significant knowledge gap regarding the Leucetta sponge in Indonesia. The objective of this study was to describe the biology of a calcareous sponge belonging to the genus Leucetta, which was collected from the Sangihe Islands in Indonesia. Morphological analysis was conducted using a modified acid digestion method, and the obtained data were compared to reported data for Leucetta sponges. The sponge exhibited triactine spicules, which are characteristic of Leucetta species. The number list of Indonesian Leucetta sponges was determined through a literature search. Previous research indicated that 40 identified calcareous sponges were reported in Indonesia between 1890 and 2023. Interestingly, L. avocado is known as a native sponge to Palau, although this species and closely related species have been reported elsewhere. Therefore, it is predicted that the current distribution of L. avocado in the Sangihe Islands and Bali could be attributed to a combination of the Indonesian Throughflow, sexual propagation, or stepping stone scenarios. This research provides new insights into the biology of L. avocado from Indonesia.